Back‐transformation mechanisms of ringwoodite and majorite in an ordinary chondrite. (27th July 2020) - Fukimoto, Kanta; Miyahara, Masaaki; Sakai, Takeshi; Ohfuji, Hiroaki; Tomioka, Naotaka; Kodama, Yu; Ohtani, Eiji; Yamaguchi, Akira
Abstract: We investigated the back‐transformation mechanisms of ringwoodite and majorite occurring in a shock‐melt vein (SMV) of the Yamato 75267 H6 ordinary chondrite during atmospheric entry heating. Ringwoodite and majorite in the shock melt near the fusion crust have back‐transformed into olivine and enstatite, respectively. Ringwoodite (Fa 18 ) occurs in the SMV as a fine‐grained polycrystalline assemblage. Approaching the fusion crust, fine‐grained polycrystalline olivine becomes dominant instead of ringwoodite. The back‐transformation from ringwoodite to olivine proceeds by incoherent nucleation and by an interface‐controlled growth mechanism: nucleation occurs on the grain boundaries of ringwoodite, and subsequently olivine grains grow. Majorite (Fs16–17 En82–83 Wo1 ) occurs in the SMV as a fine‐grained polycrystalline assemblage. Approaching the fusion crust, the majorite grains become vitrified. Approaching the fusion crust even more, clino/orthoenstatite grains occur in the vitrified majorite. The back‐transformation from majorite to enstatite is initiated by the vitrification, and growth continues by the subsequent nucleation in the vitrified majorite.